Políticas territoriais e a questão fundiária no Amapá (1970-2020) - Edmilson das Merces Batista (Confins)
From a historical-spatial approach, this paper examines how, during the decades that go from 1970 to 2020, the current land situation in Amapá has defined. Priority is described the action of the State, private capital, squatters and traditional communities, influenced in the form of distribution and concentration of land ownership. Therefore, five territorial strategies or policies, present in the agrarian issue in Amapá are described and discussed: 1) the federalization of lands; 2) the granting of public lands for large projects and agricultural companies; 3) the policy of colonization or rural settlements; 4) the regularization of squattors and the Terra Legal program; and 5) land regularization of quilombola communities.